2020
DOI: 10.9734/jerr/2020/v18i417213
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Two-parameter Weibull Distribution Method to Assess the Reliability of Gas Turbine Compressors

Abstract: In this paper, the reliability of axial compressors of gas turbines used in oil and gas installations was analyzed by the application of the two-parameter Weibull distribution method. Reliability analysis is an important tool to minimize the failures of equipment, shorten repair time and enhance maintenance effectiveness because when a system is well-maintained system, it minimizes operating costs and optimizes throughput. The study involves the analysis of the failure times of three identical gas turbine comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Keywords: petroleum engineer, Monte Carlo method, nuclear fission, gas industry, probability distribution, environmental regulation, Bayesian network, Weibull distribution, electricity distribution network, hydroelectric power, etc. This cluster mentions reliability analysis, risk management, and strategic planning in the oil and gas industry (petroleum engineer) and Hydroelectric power plant by applying Monte Carlo simulation, Bayesian network, or Weibull distribution [37]. Moreover, Monte Carlo simulation and Bayesian network methods are also employed regularly in environmental risk assessment and CM of a nuclear power plant.…”
Section: New Methods Of Clustering Keyword Co-occurrence Networkmentioning
confidence: 99%
“…Keywords: petroleum engineer, Monte Carlo method, nuclear fission, gas industry, probability distribution, environmental regulation, Bayesian network, Weibull distribution, electricity distribution network, hydroelectric power, etc. This cluster mentions reliability analysis, risk management, and strategic planning in the oil and gas industry (petroleum engineer) and Hydroelectric power plant by applying Monte Carlo simulation, Bayesian network, or Weibull distribution [37]. Moreover, Monte Carlo simulation and Bayesian network methods are also employed regularly in environmental risk assessment and CM of a nuclear power plant.…”
Section: New Methods Of Clustering Keyword Co-occurrence Networkmentioning
confidence: 99%
“…Al‐Fawzan 21 presented both graphical and analytical methods for estimation of Weibull parameters to compute reliability and concluded that the result which gives the best estimates is the method of moments. Further Ozonuwe, Onyekachi, and Oside, 22 in their research article, looked into the application of the two‐parameter Weibull distribution to assess the reliability of gas turbine compressors. The study involved the analysis of the failure times of the compressors using the median rank regression estimation method.…”
Section: Introductionmentioning
confidence: 99%